Gnarly planning : tools for local and global action - Stanley, Jane (Jane Marilyn), 1949- (Sarina, Qld. : Focus, 2007)
"Explaining planning in way which made sense to planning students, relevent to the challenges of the real world."--Provided by publisher.
Index present.
Bibliography: p. 267-273.
Keywords: Planning; City planning; Urban policy; Economic policy; Cultural policy; Decision making